Analysis of the Utilization of AI Chat GPT in the Academic Life of Prospective Mathematics Teacher Students - Muhammad Nafis Mumtaz; Iqbal Ramadani (Universitas Teknokrat Indonesia, 2025)
This study aims to analyze the utilization of ChatGPT by prospective mathematics teacher students and to examine the potential risks of using ChatGPT in coursework. A case study method with a qualitative approach is employed in this research. Data is collected through a survey, which is distributed online via Google Forms to prospective mathematics teacher students. The results indicate that ChatGPT significantly enhances learning efficiency and aids in completing assignments. However, there are concerns about potential misuse and its negative impact on critical thinking skills and academic ethics. These findings highlight the need for wise usage guidelines and education regarding the ethical use of AI technology in education.